2014
DOI: 10.1007/s00431-014-2440-1
|View full text |Cite
|
Sign up to set email alerts
|

Suffering in children: opinions from parents and health-care professionals

Abstract: Parents', physicians', and nurses' perceptions of suffering overlap but also show important differences. Differences found seem to be rooted in the relation to and kind of responsibility (parental/professional) for the child. The child's illness, suffering, and hospital admission cause suffering in parents. Health-care professionals in PICUs need to be aware of these phenomena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…In PICUs, the uncertainties entailed by death and the necessity to help the family make the complicated decision about do-not-resuscitate (DNR) orders in emergent situations may lead to moral predicaments for nurses. This finding is consistent with other studies on care experiences of NICU nurses (de Weerd, van Tol, Albers, Sauer, & Verkerk, 2015; Prentice, Gillam, Davis, & Janvier, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…In PICUs, the uncertainties entailed by death and the necessity to help the family make the complicated decision about do-not-resuscitate (DNR) orders in emergent situations may lead to moral predicaments for nurses. This finding is consistent with other studies on care experiences of NICU nurses (de Weerd, van Tol, Albers, Sauer, & Verkerk, 2015; Prentice, Gillam, Davis, & Janvier, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Study after study has demonstrated that the experience of caring for very ill children causes significant distress and often suffering in parents and caregivers, especially bedside nurses who are often the primary witnesses of patient’s day-to-day experiences. 20 24 Furthermore, the caregiver subjects of qualitative studies on perceptions of child suffering often spontaneously described their own suffering. Take the following quote as an example of parent suffering: And we, we suffer now.…”
Section: Responding To Claims Of Suffering In Pediatricsmentioning
confidence: 99%
“…Your family is now disrupted, they sleep at different places and times and sometimes you’re not always there mentally. 22…”
Section: Responding To Claims Of Suffering In Pediatricsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sedation should be optimized, but adequate dosage could significantly vary with time. 8 A complete weaning from respiratory support should be considered if the neurologic evolution remains worrisome and the child is unable to breath independently. This support could be seen as an artificial way to prolong life and could be withdrawn after the parents agree.…”
Section: Proposed Management Of This 12-year-old Girlmentioning
confidence: 99%